A Disintegrin and Metalloproteases (ADAMs) in Cardiovascular, Metabolic and Inflammatory Diseases: Aspects for Theranostic Approaches - van der Vorst, Emiel P. C.; Weber, Christian; Donners, Marjo M. P. C. (Thrombosis and Haemostasis, 2018)
A disintegrin and metalloproteases (ADAMs) are membrane-bound enzymes responsible for the shedding or cleavage of various cell surface molecules, such as adhesion molecules, cytokines/chemokines and growth factors. This shedding can result in the release of soluble proteins that can exert agonistic or antagonistic functions. Additionally, ADAM-mediated cleavage can render these membrane proteins inactive. This review will describe the role and association of ADAMs in various pathologies with a main focus on ADAM10 and ADAM17 in atherosclerosis, including a brief overview of atherosclerosis-related ADAM substrates. Furthermore, ADAMs involvement in other metabolic and inflammatory diseases like diabetes, sepsis, Alzheimer's disease and rheumatoid arthritis will be highlighted. Subsequently, we will briefly discuss an interesting emerging field of research, i.e. the potential implications of ADAM expression in extracellular vesicles. Finally, several ADAM-based therapeutic and diagnostic (theranostic) opportunities will be discussed, while focusing on key questions about the required specificity and selectivity.
Keywords: a disintegrin and metalloprotease; pathologies; cardiovascular disease; atherosclerosis; therapy